Association of Retn (Rs3219175) Polymorphism with Oscc Progression and Development - An In Silico Study - Monica.K1 , J. Vijayashree Priyadharsini2 , Gheena. S3 , Pratibha Ramani4 , Abhilasha. R5 , (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oral squamous cell carcinoma (OSCC) is more common with 90% of malignant neoplasm in oral cavity.Multiple factors leading to OSCC like genetic alterations, ?hr???? exposure, micro environmental carcinogens,premalignant disease like oral epithelial dysplasia, mitochondrial membrane damage and viruses infectionslike HPV (human papillomavirus). RETN gene belongs to the family of mouse resistin-like genes. Humangenetic variations are found to influence inter-individual variation observed in disease susceptibilities, drugresponse, response to an infectious disease. At the molecular level these sequence variations influence geneexpression, protein production, function, disease susceptibility in particular individuals. The present in silicostudy determines the possible association of RETN polymorphism with that of oral squamous cell carcinomain different populations. In this study the RETN gene polymorphism rs321975 was analysed in comparisonto the global frequencies. The present study attempts to identify the possible reason for the selection of “A”allele in the south asian population. Furthermore, genotyping analysis has to be performed in a south Indianpopulation to ascertain the association between RETN polymorphism (rs3219175) and OSCC.